2013
DOI: 10.3892/mmr.2013.1364
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid induces apoptosis via Akt/NF-κB signaling suppression in T24 human bladder cancer cells

Abstract: The Akt/NF-κB pathway is involved in numerous anti‑apoptotic and drug resistance events which occur in various types of bladder cancer. The present study investigated the role of ursolic acid in the regulation of anti-apoptotic Akt and NF-κBp65 signaling. T24 human bladder cancer cells were treated with ursolic acid at final concentrations of 12.5, 25 or 50 µmol/l for 48 h. Quantitative PCR (qPCR) and western blotting were performed to detect mRNA and protein expression, respectively. The results showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…In our work Western blotting revealed that ursolic acid cleaved PARP and caspase 3 and attenuated the expression of procaspase 9, cyclin D1, pAKT, pGSK3α/β, β-catenin and NFkB in three mesothelioma cells, demonstrating that apoptosis induced by ursolic acid was mediated via caspase activation and survival gene inhibition. Similarly, previous studies showed that ursolic acid induced apoptosis via inhibition of the Wnt5/β-catenin pathway in prostate cancer cells 17 and also inhibited the cell growth via AMPK 33, ER stress 34 or Akt/NF-kB 35 in human bladder cancer cells carcinoma cells.…”
Section: Discussionsupporting
confidence: 59%
“…In our work Western blotting revealed that ursolic acid cleaved PARP and caspase 3 and attenuated the expression of procaspase 9, cyclin D1, pAKT, pGSK3α/β, β-catenin and NFkB in three mesothelioma cells, demonstrating that apoptosis induced by ursolic acid was mediated via caspase activation and survival gene inhibition. Similarly, previous studies showed that ursolic acid induced apoptosis via inhibition of the Wnt5/β-catenin pathway in prostate cancer cells 17 and also inhibited the cell growth via AMPK 33, ER stress 34 or Akt/NF-kB 35 in human bladder cancer cells carcinoma cells.…”
Section: Discussionsupporting
confidence: 59%
“…In terms of the gastrointestinal system, UA has a direct inhibitory effect on NF-κB activation in intestinal epithelial cells stimulated by TNF-α, and in peritoneal macrophages stimulated by LPS (4). UA also suppresses NF-κB signaling in colon cancer cells (7), and other types of cancer cell (40,41). In the present study, the nuclear level of NF-κB p65 in the colon tissues of the DSS group was significantly increased, compared with that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid was proved to suppress the proliferation of colon cancer cell line HEK293 by promoting degradation of β-catenin (33). In Enrlich ascites carcinoma cell line, ursolic acid acts as an inducer of apoptosis through the mitochondrial signaling pathway in intro and in vivo (34), and in T24 human bladder cancer cells, it induces apoptosis via the Akt/ NF-κB pathway (35). Ursolic acid also can induce cell death and modulate autophagy by the JNK pathway in the apoptosis-resistant human colon carcinoma cell line HCT15 and CO115 (36).…”
Section: Triterpenementioning
confidence: 99%